BIOACCUMULATION OF SOME METALS IN THE FISH SAROTHERODON GALILAEUS CAUGHT FROM ALARO STREAM IN IBADAN (2016)
Studies were carried out on the bioaccumulation of some metals in the fish Sarotherodon galilaeus caught from Alaro Stream in Ibadan. Previous studies have shown that fish can bioaccumulate and retain some metals from their environment which is dependent on exposure concentration, temperature, water hardness and metabolism of the animals, duration, as well as other factors such as salinity and lipid levels. In this study, the bioaccumulation of the some metals namely sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), silver (Ag) and zinc (Zn) in the fish Sarotherodon galilaeus caught from Alaro Stream in Ibadan was studied to ascertain the health risks associated with human consumption of the fish. The results showed that all the mean Na in the organs and tissues of S. galilaeus exceeded the recommended taste limit of 200 ppm. The highest mean Mg was in the bone (2684 ppm) while the lowest was 498 ppm (muscle) in the order: muscle<liver<gut<gills<fins<bone. The highest mean K was 16143 ppm (gut) while the lowest was 14426 ppm (muscle) while the highest Ca level was 73216 ppm (bone) and the lowest mean was recorded in the gills (2806 ppm) in the order: gills<liver<muscle <fins<gut<bone. With the exception of the gut (0.55 ppm), all the other organs had mean Ag below the World Health Organization permissible limit guideline standard of 0.1 ppm. All the mean Zn levels in the organs and tissues of S. galilaeus were above the WHO permissible limit guideline standard of 5 ppm. Moderation in the consumption of the fish S. galilaeus caught from Alaro Stream is recommended